2018
DOI: 10.1152/ajprenal.00179.2018
|View full text |Cite
|
Sign up to set email alerts
|

Divergent effects of AKI to CKD models on inflammation and fibrosis

Abstract: Chronic kidney disease (CKD) is a condition with significant morbidity and mortality that affects 15% of adults in the United States. One cause of CKD is acute kidney injury (AKI), which commonly occurs secondary to sepsis, ischemic events, and drug-induced nephrotoxicity. Unilateral ischemia-reperfusion injury (UIRI) without contralateral nephrectomy (CLN) and repeated low-dose cisplatin (RLDC) models of AKI to CKD demonstrate responses characteristic of the transition; however, previous studies have not effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 61 publications
6
50
0
Order By: Relevance
“…Such a scenario is more representative of chemotherapeutic low-dose cisplatin administered over an extended period of time, whereby sustained inflammation is a contributing factor to the transition from AKI to renal fibrosis and CKD (14). Our 4x 5 µM approach is also consistent with recent work in mice, where repeated low-dose cisplatin regimens were shown to induce inflammatory cytokines and fibrosis markers in contrast to the acute toxicity, high mortality and lack of fibrosis seen with a single high-dose treatment (1,3,15).…”
Section: Discussionsupporting
confidence: 82%
“…Such a scenario is more representative of chemotherapeutic low-dose cisplatin administered over an extended period of time, whereby sustained inflammation is a contributing factor to the transition from AKI to renal fibrosis and CKD (14). Our 4x 5 µM approach is also consistent with recent work in mice, where repeated low-dose cisplatin regimens were shown to induce inflammatory cytokines and fibrosis markers in contrast to the acute toxicity, high mortality and lack of fibrosis seen with a single high-dose treatment (1,3,15).…”
Section: Discussionsupporting
confidence: 82%
“…Hence, we utilized another well-established model of kidney injury induced by the administration of cisplatin in the context of both AKI and CKD. To this end a single injection of 20 mg/kg of cisplatin was used to induce AKI (high dose, HD), while repeated dosing of 9 mg/kg of cisplatin was administered once a week for 4 weeks to induce CKD (repeated low dose, RLD) as previously reported [23, 24]. For the AKI studies, tissues were harvested at 72h post injury, while CKD studies were terminated at 28 days.…”
Section: Resultsmentioning
confidence: 99%
“…These animals were sacrificed 72 hours after injection. For the repeated low dose (RLD) model, age-matched C57BL/6 male mice (10–12 weeks of age) were briefly anesthetized with isoflurane, and 9 mg/kg body wt cisplatin (1.0 mg/ml solution in sterile 0.9% saline) were administered intraperitoneally once a week for 4 wk, adapted from Sharp et al and Black et al [23, 24].…”
Section: Methodsmentioning
confidence: 99%
“…The pathophysiological changes of CKD, such as the activation of TGF- β , p53, and HIF pathways in kidney and CKD related chronic inflammation and vascular dysfunction, might contribute to the severe AKI progress [ 30 ]. On the contrary, some clinical studies found that KIM-1 did not provide robust prognostic information on the loss or renal function in CKD population [ 31 , 32 ]. Since the sample size was small in Wang et al [ 10 ] research, studies with a larger sample size are needed to clarify this problem.…”
Section: Discussionmentioning
confidence: 99%